Autologous hematopoietic stem cell transplantation for efficient treatment of multisystem, high-risk, BRAF V600E-negative Langerhans cell histiocytosis. Issue 9 (September 2019) - Pan, Yaozhu; Xi, Rui; Wang, Cunbang; Fang, Lei; Bai, Jiaofeng; Cai, Yonggang; Guo, Min; Qiao, Ruiyun; Lan, Xu; Yin, Jiaojiao; Yang, Ke; Bai, Hai
Langerhans cell histiocytosis (LCH) is a disorder caused by clonal proliferation of CD1a + /CD207 + cells and characterized by varying degrees of organ involvement. Treatment of LCH is risk adapted; patients with multisystem disease and risk-organ involvement require more intensive therapy. Optimal therapies for multisystem, high-risk LCH remain uncertain. Recently, targeted therapy using inhibitors of mutated BRAF (the gene encoding serine/threonine-protein kinase B-Raf) has proven very effective in patients with multisystem refractory LCH. Herein, we report a case of LCH with involvement of the bones, liver, and lymph nodes. Using next-generation sequencing of the patient's pathological sample, we identified a mutation in MAP2K1 in exon 3 (c.362G>C, p.Cys121Ser) and no mutation in BRAF ; thus, high-risk, multisystem LCH with MAP2K1 mutation and wild-type BRAF was diagnosed. After four chemotherapy treatments (COEP regimen), the patient received autologous hematopoietic stem cell transplantation (auto-HSCT). Complete remission was confirmed by follow-up positron emission tomography–computed tomography, which showed no lesions in liver, lymph nodes, or bones compared with the pretreatment period. To date, the patient has sustained good health for 24 months. In conclusion, auto-HSCT may be an effective treatment option for high-risk, multisystem BRAF V600E-negative LCH.